KHASANAH KEDAULATAN DALAM REGIONALISME DI ERA GLOBALISASI (Studi Kasus Implementasi ACFTA Di Indonesia) - Rindu SM Firdaus (Jurnal Ketahanan Nasional, 2013)
This paper explained the state sovereignty in globalization context, the qualitative data showed globalization practice paradox on economic resilience and Indonesia national security. The economic terms showed the ACTFA had weakened wealth values and state sovereignty. However globalization also had chances for a state to enhance its economic fortune with trading efficiency enhancement and global market extension. Economic cooperation especially in free trade regionalism would enhance the burgeoning position due the open cooperation of the global powers such as China with ACTFA. The security terms showed economic transformation into modern imperialism devices as the power activator and others pressure, which named as capitalist imperialism.Keywords: State Sovereignty, Regionalism, ACTFA, and Globalization.